1999
DOI: 10.1016/s0010-4655(99)00293-3
|View full text |Cite
|
Sign up to set email alerts
|

Emergence and growth of complex networks in adaptive systems

Abstract: We consider the population dynamics of a set of species whose network of catalytic interactions is described by a directed graph. The relationship between the attractors of this dynamics and the underlying graph theoretic structures like cycles and autocatalytic sets is discussed. It is shown that when the population dynamics is suitably coupled to a slow dynamics of the graph itself, the network evolves towards increasing complexity driven by autocatalytic sets. Some quantitative measures of network complexit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 7 publications
0
27
0
Order By: Relevance
“…We denote 1 (C) ϵ 1 . It can be shown (16) that if the graph does not have an ACS, then 1 ϭ 0, and if it does, then 1 Ն 1.…”
Section: Definitions and Notationmentioning
confidence: 99%
See 1 more Smart Citation
“…We denote 1 (C) ϵ 1 . It can be shown (16) that if the graph does not have an ACS, then 1 ϭ 0, and if it does, then 1 Ն 1.…”
Section: Definitions and Notationmentioning
confidence: 99%
“…Dominant ACS. It can be shown that if 1 Ն 1 the subgraph comprising the populated species (X i Ͼ 0) must be an ACS (11,16), which will be referred to as the dominant ACS. The dominant ACS is uniquely determined by the graph and does not depend on the initial condition for x (except for special initial conditions forming a set of measure zero, which we ignore).…”
Section: Definitions and Notationmentioning
confidence: 99%
“…(see [5,16] Further, Tahir et al [15] introduced fuzziness into an autocatalytic set. The definition for fuzzy autocatalytic set is given as below: Definition 9.…”
Section: Fuzzy Autocatalytic Setmentioning
confidence: 99%
“…The initial graph is chosen such that for all i j a t ij ϭ 1 with probability q and a t ij ϭ 0 with probability 1 Ϫ q. This model has been introduced in Jain and Krishna [17], based on the well-documented Bak-Sneppen model of evolution [11], and its properties have extensively been investigated in the literature [12][13][14][15][16], besides others.…”
Section: The Modelmentioning
confidence: 99%